THE PROBLEM OF ACCELERATING THE ITERATION PROCESS IN SOLUTION OF THE DIRAC EQUATION - Abdunazarov Rabimkul; Sharipova Sadoqat; Kudaikulov Anarbay Kudaikulovich (Web of Journals Publishing, 2024)
This paper proposes an accelerated algorithm for solving the Dirac equation. The advantage of this method is that, thanks to the successful organization of the iterative process, a significant part of the found approximate solution is expressed through an elementary function.
Keywords: Dirac equations, eigenvalues, eigenfunctions, Dirac systems, successive approximation method.